Indirect spectrophotometric determination of folic acid based on the oxidation reaction and studying some of the thermodynamic parameters - Othman, N S.; Hasan, Sh H.; Surchi, K M. (Sulaimani Journal for Pure and Applied Sciences, 2015)
A simple and sensitive indirect spectrophotometric method was developed for the determination of folic acid in pure form and in its pharmaceutical formulations. The method was based on the oxidation of folic acid by iron (III) in acidic medium, then reaction of liberated iron (II) with 2, 2'-bipyridyl to produce a red complex which is water-soluble, stable, and has a maximum absorption at 520 nm against the reagent blank with a molar absorptivity of 2.8338 x 105 L .mol-1.cm-1. Beer’s law is valid over the concentration range of 0.5-18.0 µg/ml folic acid. The values of some thermodynamic parameters [free energy change (∆G), enthalpy change (∆H), and entropy change (∆S)] were estimated from the values of stability constants (K) at different temperatures .It was found that colored product formation was spontaneous, exothermic and accompanied by an increase of random. The proposed method has been applied successfully to determine folic acid in different pharmaceutical preparations.
Keywords: Spectrophotometry; Folic acid; 2,2BipyridylFeCl3 Thermodynamic; Parameters